NPK uptake and growth of maize on ombrogenous peat as affected by the application of mycorrhizal fungal multi-spores and compound fertilizers - Angga Ade Sahfitra; Eko Hanudin; Cahyo Wulandari; Sri Nuryani Hidayah Utami (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
This study investigated the effectiveness of mycorrhizal fungal multi-spores and inorganic fertilizers in increasing NPK uptake and growth of maize on ombrogenous peat soils in Riau. The experiment, which was carried out in a plastic house, was arranged in a completely randomized design (CRD) with two factors, consisting of five replications. The first factor was the application of mycorrhizal fungal multi-spores, consisting of two levels (with and without application). The second factor was the application of inorganic fertilizer, consisting of three levels (P0: without fertilizer, PM-1: mixture of 225 kg Urea + 100 kg SP-36 + 75 kg KCl + 1000 kg Dolomite, and PM-2: mixture of 450 kg Urea + 200 kg SP-36 + 150 kg KCl +2000 kg Dolomite). Observed data consisted of agronomic observations, soil observations, and mycorrhiza observations. Agronomic observations consisted of plant height, root dry weight, shoot dry weight, and N, P, K nutrient uptake, and soil observations consisted of total and available N, P, K nutrients in the soil. Meanwhile, mycorrhiza observations consisted of infected roots and spore populations. The data obtained were then analyzed using DMRT to see the significant effect of the treatments. There was no interaction effect of mycorrhiza and compound fertilizer on the variables of shoot and root dry weight, but the interaction effect was observed on the variables of of shoot N, P, K uptake and root P and K uptake.